Differential Expression Profiles and Functional Prediction of Circular RNAs in Pediatric Dilated Cardiomyopathy - Sun, Wei; Han, Bo; Cai, Dongxiao; Wang, Jing; Jiang, Diandong; Jia, Hailin (Frontiers in Molecular Biosciences, 2020)
Circular RNAs (circRNAs) have emerged as essential regulators and biomarkers in various diseases. To assess the different expression levels of circRNAs in pediatric dilated cardiomyopathy (PDCM) and explore their biological and mechanistic significance, we used RNA microarrays to identify differentially expressed circRNAs between three children diagnosed with PDCM and three healthy age-matched volunteers. The biological function of circRNAs was assessed with a circRNA–microRNA (miRNA)–mRNA interaction network constructed from Gene Ontology and the Kyoto Encyclopedia of Genes and Genomes. Differentially expressed circRNAs were validated by quantitative real-time polymerase chain reaction (qRT-PCR) in 25 children with PDCM and 25 healthy volunteers. We identified 257 up-regulated (fold change ≤ 0.5, P < 0.05) and 899 down-regulated (fold change ≥2, P < 0.05) circRNAs in PDCM patients when compared to healthy volunteers. The qRT-PCR experiments confirmed has_circ_0067735 down-regulation (0.45-fold, P < 0.001), has_circ_0070186 up-regulation (2.82-fold, P < 0.001), and has_circ_0069972 down-regulation (0.50-fold, P < 0.05). A functional analysis of these differentially expressed circRNAs suggests that they are associated with hypertrophy, remodeling, fibrosis, and autoimmunity. CircRNAs have been implicated in PDCM through largely unknown mechanisms. Here we report differentially expressed circRNAs in PDCM patients that may illuminate the mechanistic roles in the etiology of PDCM that could serve as non-invasive diagnostic biomarkers.